Proximal-distal anatomical relationships between spermatocysts (Sertoli – germ cell units) and eosinophilic immune system elements in the shark testis: A comparative study of the Greenland shark and thresher shark - Leon Mendel McClusky (Theriogenology Wild)
Despite lacking a voluminous testis-associated lymphomyeloid tissue (epigonal organ) in adulthood, the far distally located non-spermatogenic tissue of the wild-captured Greenland shark (Somniosus microcephalus) houses loosely circumscribed, granulocyte-liberating epigonal cell patches. These dynamic patches of epigonal cells are coincident with the differentiation and subsequent distribution of two types of intravascular and extravascular eosinophilic granulocytes in the expansive non-spermatogenic tissue, and in the interstitium of notably premeiotic and meiotic stages of spermatogenesis. Their sparse numbers, discreet occurrence, and as a rule within the vicinity of a blood vessel in all examined tissue samples, including a 1960s archival collection of tissues, are indicative of diapedesis whereupon they become ensconced in the tight interstitial spaces of spermatocysts (stage-synchronized germ and Sertoli cell clones). By comparison, an anatomically robust and intimate testis – epigonal association in the thresher shark does not correlate with any type of granulocyte in the testicular parenchyma nor its vasculature, despite that the most proximal eosinophilic epigonal cells nearly abut the basement membrane of some of its spermatozoal cysts (the only cyst stage to reveal this). These findings in Somniosus are discussed in relation to the previously reported protracted phase of disordered internal cellular organization of the Greenland shark’s spermatogonial cysts due to incompletely differentiated Sertoli supportive functions for what should be well-advancing spermatogonial generations.